Numerical simulations for the equilibrium state and solution behaviors in the multi-phase catalytic reaction mechanism. (November 2020) - Shahzad, Muhammad; Sultan, Faisal; Ali, Mehboob; Tauseef, Isfahan; Ahmed, Shehzad
Abstract: According to Horiuti rule, the higher-dimensional catalytic complex chemical problems are split down in different possible reaction routes. This will remove the stiffness of the system and allows us to analyze the distinct behavior of the catalytic and non-catalytic species during the reaction as well as the whole reaction mechanism. The construction and comparison of the multi-invariant region and 1D and 2D curves (manifold) require detailed analysis of the system and have never been reported so far. The purpose of writing this article is, to find and compare the transition period of the chemical species and solution trajectories of the multi-phase reaction mechanism through the model reduction technique (MRT), i.e., Spectral Quasi Equilibrium Manifold (SQEM) for multi-route reaction mechanisms. For convenience, a multi-step chemical reaction mechanism over the closed system is considered in detail and the results are obtained through programming in MATLAB.